Melatonin mediates phenolic acids accumulation in barley sprouts under MeJA stress - Tian, Xin; Zhang, Renjiao; Yang, Zhengfei; Zhu, Jiangyu; Fang, Weiming; Yang, Runqiang; Yin, Yongqi (Frontiers in Nutrition, 2024)
Phenolic acids are secondary metabolites in higher plants, with antioxidant, anticancer, and anti-aging effects on the human body. Therefore, foods rich in phenolic acids are popular. Methyl jasmonate (MeJA) promoted phenolic acids accumulation but also inhibited sprout growth. Melatonin (MT) was a new type of plant hormone that not only alleviated plants’ abiotic stress, but also promoted the synthesis of plant-stimulating metabolism. This study aimed to elucidate the mechanism of exogenous MT on the growth and development, and phenolic acids metabolism of barley sprouts under MeJA treatment. The results showed that MT increased the phenolic acids content in sprouts by increasing the activities of phenylalanine ammonia-lyase and cinnamic acid 4-hydroxylase, and up-regulating the gene expression of phenylalanine ammonia-lyase, cinnamic acid 4-hydroxylase, 4-coumarate: coenzyme a ligase, and ferulic acid-5-hydroxylase. MT attenuated the growth inhibition of barley sprouts under MeJA stress by increasing the activities of regulated antioxidant enzymes and the expression of their corresponding genes. Furthermore, MT increased the NO content and induced Ca2+ burst in barley sprouts under MeJA stress. These events were inhibited by DL-4-Chlorophenylalanine. These results suggested that MT ameliorated growth inhibition and promoted the biosynthesis of phenolic acids in barley sprouts under MeJA stress.